Analisis Teknik Pemotongan Rambut Gradasi sebagai Dasar Keterampilan Tata Kecantikan - Listiana, Ridainisa Dwi; Legawa, Kayla Putri; Khofifah, Anita Nur; Hasanah, Selvi Hasnita; Munaf, Adinda Talitha Syahada; Rahmadiansyah, Hemalia Ayu; Putri, Indah Selfiana; Putri, Intan Aulia; Fitriani, Farida; Elby, Queenasyifa Sakinata; Nabila, Ayesha; Azura, Octavina; Rafila, Firyal Usda; Nefi, Rosa; Yuniarti, Wanda Anggi; Angellita, Vivian Nur; Nurhayati, Ifa (Universitas Negeri Semarang, 2025)
This study aims to analyze the application of graduation haircut techniques as a foundational skill in beauty and hairdressing for students. This research employed a descriptive qualitative method using a case study design. Data were collected through lecturer explanations during demonstrations of graduation techniques, observations of third-semester students’ haircutting practices, and photographic documentation of haircuts, analyzed in terms of neatness, shape, and technique accuracy. The results indicate that most students were able to apply graduation techniques effectively, particularly in maintaining the basic haircut line. However, weaknesses were observed in the symmetry between the left and right sides of the hair, suggesting the need for repeated practice and intensive guidance. Observations also highlighted that mastery of technical aspects such as cutting angles, body posture, and hairpulling direction is crucial in determining the quality of the haircut. Mastering graduation techniques not only enhances students’ technical skills but also prepares them to meet the demands of the salon industry, where clients expect neat, symmetrical, and trendy haircuts. Therefore, repeated practice, periodic evaluation, and the use of supplementary learning media are essential strategies to improve students’ competence. Based on the findings, it is recommended that students continue practicing, develop the ability to adapt graduation techniques to different hair characteristics, and understand client needs to compete professionally in the salon industry.